THE ROLE OF METABOLIC SYNDROME IN THE ALZHEIMER’S DISEASE - Emanuel Mendes da Silva Santos, Arlys; Maria Senhorinha, Gláucia; Thaine Teodoro, Danielly; Ferreira Firmino, Fernanda; Cerqueira Simões Braudes, Isadora; Sena de Lucena, Larissa (Health and Society, 2021)
INTRODUCTION Alzheimer’s disease (AD) is characterized by progressive cognitive loss coupled with age-related functional impairment. Its two major brands are β-amyloid plaques and neurofibrillary tangles. There is strong evidence for a relationship between Metabolic Syndrome (MS) and AD. Both pathologies are quite prevalent and dependent on aging. OBJECTIVE The present study seeks to understand the role of the metabolic syndrome in the pathophysiology of Alzheimer’s disease and to describe preventive and therapeutic interventions. METHODOLOGY The review was made based on the search for scientific articles in the electronic databases PUBMED and Web of Science, using the descriptors “Alzheimer’s Disease”, “Metabolic Syndrome” DISCUSSION MS is a metabolic breakdown with the potential to damage insulin signaling in the brain, causing insulin resistance, inhibiting β-amyloid clearance and its accumulation, which generates neuroinflammation. In addition, it induces a prothrombotic state with ischemic effects, resulting in oxidative stress and neuroinflammation and progressive local brain atrophies. The components of the metabolic syndrome are related to AD, exacerbating neuroinflammation and insulin resistance. Preventive and therapeutic measures aiming at the MS are promising. CONCLUSION From the analyzes developed in this study, different relationships between the components of MS and AD are perceived, the first being possible causes and / or effects of the second. Since insulin resistance plays a major role in the initiation and perpetuation of cognitive impairment in AD. Furthermore, the components of MS associated with AD, when treated with preventive and therapeutic measures, break this association by promoting rebalancing of the metabolism.